Mindful consumption towards investment funds in Malaysia: evidence from Islamic and conventional financial institutions / Dr. 'Ismah Osman … [et al.] - Osman, 'Ismah; Syed Alwi, Sharifah Faigah; Muda, Ruhaini; Mohamad, Saadiah; Abd Malek, Ahmad Baihaqi (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
There is an increasing demand for fund investments among Muslim and non-Muslim investors. More importantly, there is a need to convert those ethical investment into shari'ah-compliant investment, hence, increasing the size of the shari'ah-compliant products worldwide. Apparently, the concept of mindful consumption developed by Sheth et al. (2011) would be the central point for the study. It is related to caring for one-self, the community, as well as the environment (Sheth et al., 2011). Consequently, social cognitive theory and theory of planned behaviour are used towards mindful-consumption modelling among Malaysian investors. Interviews will then be conducted, and consecutively, mindful-consumption measurement scale will be further developed. It is anticipated that by incorporating mindful consumption in this study, some of the reasons towards the consumption of ethical investment can be determined and subsequently, relevant strategies and policies can further be strengthened